HOPFIT: A neuro-cardiovascular monitoring framework for precision sedation, anaesthesia, and resuscitation - Andrea Lavinio; Stefano Romagnoli; Basil Matta (Journal of Clinical Monitoring and Computing, 2026)
Abstract The increasing availability of advanced monitoring technologies in anaesthesia and critical care has enabled continuous assessment of neurological, haemodynamic, and oxygen delivery parameters. Despite this, integrating multiple data streams into coherent, physiology-guided clinical decisions remains challenging, and unified interpretive frameworks remain limited. To introduce the HOPFIT framework — a conceptual model linking continuous neuro-cardiovascular monitoring to structured, physiology-guided clinical reasoning across six interdependent domains. HOPFIT organises six therapeutic domains — Hypnotics, Opioids, Pressors, Fluids, Inotropes, and Transfusion — around the interdependence of brain function, cardiovascular physiology, and oxygen delivery. Rather than introducing new monitoring modalities, the framework provides a unifying structure for bedside interpretation of existing data, including processed electroencephalography, cerebral oximetry, dynamic indices of fluid responsiveness, non-invasive haemoglobin, and cardiac output monitoring. An original pharmacodynamic risk surface illustrates the interaction between hypnotic and analgesic agents, and a conceptual hypotension framework integrating EEG and haemodynamic data illustrates how multimodal information may support clinical reasoning. Tables summarise monitoring parameters, commonly used ranges, and potential clinical applications across patient groups. HOPFIT is intended as a conceptual and educational tool to support integration of multimodal physiological data at the bedside, rather than a prescriptive clinical protocol. Prospective studies are required to determine its impact on clinical decision-making and patient outcomes.